72 Hours Standby Time of Wet-Primed Cardiopulmonary Bypass Circuits: A Microbiological Quality Assurance Study - Schulz-Stübner, Sebastian; Schorer, Cornelia; Ennker, Jürgen; Bauer, Stefan; Schaumann, Reiner (The Thoracic and Cardiovascular Surgeon, 2014)
In a microbiological sample study of 15 wet-primed cardiopulmonary bypass circuits in standby mode for 72 hours under regular clinical conditions, no contamination of the priming fluid or the connectors could be detected. Hand contact surfaces of the machines demonstrated environmental microorganisms. These findings indicate the safe use of primed cardiopulmonary bypass circuits in standby mode for 72 hours. A surface disinfection of hand contact surfaces immediately before use is recommended.
Keywords: cardiopulmonary bypass; infection; off-pump surgery; surgery; complications